2012
DOI: 10.1182/blood-2011-09-382770
|View full text |Cite
|
Sign up to set email alerts
|

5-azacytidine and decitabine exert proapoptotic effects on neoplastic mast cells: role of FAS-demethylation and FAS re-expression, and synergism with FAS-ligand

Abstract: IntroductionSystemic mastocytosis (SM) is a myeloid neoplasm characterized by pathologic accumulation of mast cells (MCs) in one or more extracutaneous organs. 1,2 Indolent and aggressive variants of SM have been described. [1][2][3][4][5] In most patients, the transforming KIT mutation D816V is detectable independent of the category of SM. [6][7][8] Patients with indolent SM (ISM) have an excellent prognosis with normal or near-normal life expectancy. [1][2][3][4][5]9,10 In patients with aggressive SM (ASM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
3
27
0
1
Order By: Relevance
“…Indeed, azacitidine favors the re-expression of FAS in neoplastic mast cells or PI-PLCbeta1 genes in MDS or sAML. 7,12 Here we show that the in vivo use of the drug also favors the re-appearance of Fas receptor in sAML-derived CD45 lo /CD34 þ cells, together with FAS promoter demethylation (Supplementary Figure S1).…”
Section: Letters To the Editormentioning
confidence: 72%
See 3 more Smart Citations
“…Indeed, azacitidine favors the re-expression of FAS in neoplastic mast cells or PI-PLCbeta1 genes in MDS or sAML. 7,12 Here we show that the in vivo use of the drug also favors the re-appearance of Fas receptor in sAML-derived CD45 lo /CD34 þ cells, together with FAS promoter demethylation (Supplementary Figure S1).…”
Section: Letters To the Editormentioning
confidence: 72%
“…7,11 The mechanism by which FAS promoter is overmethylated in sAML is still unclear. However, the 5 0 -CpG1-8 are located immediately downstream of the docking site of Dnmt1, which promotes FAS promoter methylation in KRAS-transformed NIH3T3 cells.…”
Section: Letters To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that 5-azacytidine and decitabine can induce apoptosis in the neoplastic mast cells through re-expression of Fas receptor (Ghoshal et al 2005). It has also been shown that 5-azacytidine treatment leads to apoptosis of both myeloid precursor PC-MDS cells and leukemia K562 cells, mainly through the induction of Bak mRNA expression (Ghanim et al 2012). Dihydro-5-azacytidine (DHAC) is hydrolytically more stable (Beisler et al 1977) and less cytotoxic (Presant et al 1981) than 5-Aza-CR, and has been proved to be an inhibitor of DNA methylation in human lymphoid and leukaemia cell lines, as well as in tumour-bearing mice (Antonsson et al 1987;Powell and Avramis 1988;Kees and Avramis 1995).…”
Section: Cancer Epigenetics Therapy Dna Methylation Inhibitorsmentioning
confidence: 99%